Peran Guru dalam Mengembangkan Kecerdasan Emosional Anak Usia Dini di TK Cinta Bunda Batu Bara - Eliana, Eliana; Rahman, Mhd Habibu (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the role of teachers in developing emotional intelligence in early childhood at Cinta Bunda Kindergarten in Batu Bara. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation. The results indicate that teachers have a good understanding of the importance of emotional intelligence and actively integrate it into learning activities. The role of teachers is reflected in several aspects, namely as emotional models, facilitators of play and socialization activities, providers of individualized approaches through emotional dialogue, and providers of positive reinforcement for good emotional behavior. Furthermore, teachers also collaborate with parents to consistently support children's emotional development at home. This study concludes that the active role of teachers significantly influences children's ability to recognize, manage, and express emotions in a healthy manner, which in turn positively impacts children's abilities to manage stress, communicate, and build social relationships. Implications of this study emphasize the importance of teacher training in socio-emotional aspects and synergy between schools and families in shaping children's character from an early age.